2021
DOI: 10.3389/fpsyt.2021.628933
|View full text |Cite
|
Sign up to set email alerts
|

Monetary Reward Discounting, Inhibitory Control, and Trait Impulsivity in Young Adults With Internet Gaming Disorder and Nicotine Dependence

Abstract: Internet Gaming Disorder (IGD) has been considered a potential behavioral or non-substance addiction that requires further investigation. Recognition of the commonalities between IGD and Substance Use disorders (SUD) would be of great help to better understand the basic mechanisms of addictive behaviors and excessive Internet gaming. However, little research has targeted a straightforward contrast between IGD and SUD on neuropsychological aspects. The present study thus aimed to explore the associations of rew… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 128 publications
4
10
0
Order By: Relevance
“…It is important to weigh this information, particularly on attention and the tendency to act quickly, having in mind that video games are well known to improve certain cognitive functions including attention, spatial cognition and response time [ 68 , 69 , 70 ]. These results are consistent with those of previous studies that used a different measure of impulsivity but found a higher proportion of dysfunctional gamblers to act recklessly, particularly in response to negative affect [ 21 ], and more specifically to show both abnormalities in reward systems and inhibitory control [ 65 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…It is important to weigh this information, particularly on attention and the tendency to act quickly, having in mind that video games are well known to improve certain cognitive functions including attention, spatial cognition and response time [ 68 , 69 , 70 ]. These results are consistent with those of previous studies that used a different measure of impulsivity but found a higher proportion of dysfunctional gamblers to act recklessly, particularly in response to negative affect [ 21 ], and more specifically to show both abnormalities in reward systems and inhibitory control [ 65 ].…”
Section: Discussionsupporting
confidence: 92%
“…Since pretty much all facets of impulsivity have correlated to each criterion of the DAS, we will focus on the results of the logistic regression, which takes into account the other variables in the model. These links between impulsivity assessed by the BIS-10 and the severity of dysfunctional gaming have been previously reported [ 9 , 64 , 65 ]. Regarding attentional impulsivity, which reflects difficulty maintaining attention to relevant details [ 66 ], it predicted significantly negative consequences.…”
Section: Discussionsupporting
confidence: 73%
“…Years later, Young defined problematic internet use as the inability of some people to control their own internet use, leading to disruption and impairment of their work, social and personal commitments [3]. Since then, several studies have been concerned with analyzing which variables may determine problematic Internet use [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Although there are numerous studies related to problematic Internet use, there is little empirical research based on studying the relationship between problematic use and executive functions [16]. Despite this, some studies have established a relationship between problematic Internet use and the presence of a deficit in inhibitory control, especially in relation to online gaming addiction [5,6,17]. In other words, a significant relationship has been observed between problematic Internet use, highlighting deficient self-regulation due to compulsive Internet use, and inhibition, establishing that the greater the daily use of the Internet, the lesser the capacity to manage inhibitory control [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, executive function can prevent the development of addiction by inhibiting impulsive and controlling behaviors, whilst degradation of executive function leads to an increase in impulsive behaviors and addiction development ( 16 ). Meanwhile, excessive online gaming could be detrimental to executive function, consequently spiraling without control and leading to impulsive behaviors ( 17 ). In essence, executive function plays a key role in IGA mitigation and mental health.…”
Section: Introductionmentioning
confidence: 99%